Elaboration, Collaboration, And Contribution Of Traditional Law In Indonesian National Legal System - Yohanes Firmansyah; Michelle Angelika S; Hanna Wijaya; Yana Sylvana (International Journal of Social Science and Religion (IJSSR), 2021)
Indonesia uses customary Law as positive Law in the archipelago, is obeyed and implemented as a custom, from generation to generation respected by the community as a national tradition. As a rule of Law, Indonesia adheres to many legal systems at the same time that lives and develops in society, namely the civil law system and the customary law system. All these legal systems are complementary, harmonious, and romantic. As the original Law that grows and develops from community habits, Customary Law affects the process of law enforcement in Indonesia. The values ​​contained in customary Law in Indonesia were used in the formation of jurisprudence in the Supreme Court. This paper will explain how customary Law, which has an "unwritten" character, can fill the Indonesian civil law system's legal gap. This paper's research method is a normative legal research method and uses several approaches, namely the statutory approach, the comparative approach, and the historical approach. This paper concludes that legal pluralism in Indonesia can be a solution to the legal gap created by the rigidity of civil law application.